The Copenhagen Consensus Conference 2016: children, youth, and physical activity in schools and during leisure time. Issue 19 (27th June 2016) - Bangsbo, Jens; Krustrup, Peter; Duda, Joan; Hillman, Charles; Andersen, Lars Bo; Weiss, Maureen; Williams, Craig A; Lintunen, Taru; Green, Ken; Hansen, Peter Riis; Naylor, Patti-Jean; Ericsson, Ingegerd; et al.
Abstract : From 4 to 7 April 2016, 24 researchers from 8 countries and from a variety of academic disciplines gathered in Snekkersten, Denmark, to reach evidence-based consensus about physical activity in children and youth, that is, individuals between 6 and 18 years. Physical activity is an overarching term that consists of many structured and unstructured forms within school and out-of-school-time contexts, including organised sport, physical education, outdoor recreation, motor skill development programmes, recess, and active transportation such as biking and walking. This consensus statement presents the accord on the effects of physical activity on children's and youth's fitness, health, cognitive functioning, engagement, motivation, psychological well-being and social inclusion, as well as presenting educational and physical activity implementation strategies. The consensus was obtained through an iterative process that began with presentation of the state-of-the art in each domain followed by plenary and group discussions. Ultimately, Consensus Conference participants reached agreement on the 21-item consensus statement.